Synthesis by ring closing metathesis and properties of an electroactive calix[6]arene [2]catenane. Issue 5 (2nd June 2016) - Orlandini, Guido; Zanichelli, Valeria; Secchi, Andrea; Arduini, Arturo; Ragazzon, Giulio; Credi, Alberto; Venturi, Margherita; Silvi, Serena
Abstract: Tris-( N -phenylureido)-calix[6]arenes are heteroditopic non-symmetric molecular wheels that, in apolar media, bind viologen-based molecular axles in a pseudorotaxane-type fashion. Because of the precise kinetic requirements associated with the threading process, in apolar solvents, the dicationic portion of the axle enters the calixarene annulus exclusively from the upper rim. With the general aim to develop new prototypes of molecular devices and machines whose functions could be governed through a wider set of control elements, we envisaged that the unique properties of these calixarene wheels could be transferred to the synthesis of new catenanes for the construction of unidirectional rotary motors. Herein, we describe the synthesis of a tris( N -phenylureido)calix[6]arene-based catenane by applying the intramolecular ring-closing metathesis reaction for the catenation step on a pre-formed pseudorotaxane. Abstract :